International Integration of Commodity Markets - Jain, Arvind K. (Journal of International Business Studies, 1981)
Relying on the properties of integrated markets, this paper analyzes price changes in commodity futures markets in 2 countries to test whether these markets are integrated. Statistical analysis shows that markets are integrated only imperfectly. The results shed considerable doubt on the use of the integrated markets assumption of economic analysis which deals in differentiable real goods.